Faktor-Faktor yang Berpengaruh Terhadap Loyalitas Perawat di Rumah Sakit Mitra Plumbon Indramayu - Atikah Indra Iriani; Ahdun Trigono; Dicky Yulius (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Human resource management in an organization is a complex matter. This is evidenced by the phenomenon of increasing employee turnover at Indramayu Mitra Plumbon Hospital, which rose by up to 49% in 2024. The decline in employee performance, lack of initiative, poor coordination among employees, low awareness of work professionalism, and high levels of responsibility reflect issues related to work motivation, workload, work ethic, and work stress—factors that are associated with low nurse loyalty at Mitra Plumbon Hospital. The purpose of this study is to examine the influence of work motivation, workload, work ethic, and work stress on nurse loyalty at Mitra Plumbon Hospital. Data were collected by distributing questionnaires to 110 employees of Mitra Plumbon Hospital using simple random sampling. The findings indicate that the workload at RS Mitra Plumbon is considerably high, leading to burnout and fatigue among nurses. Despite these conditions, nurses remain in their positions as they perceive the profession to be a calling, a noble vocation, and one that yields a broad societal impact. However, the low level of continuance commitment suggests that nurses may consider seeking employment at other hospitals should more attractive opportunities become available.